A chemiluminescence sensor for determination of lysozyme using magnetic graphene oxide multi-walled carbon nanotube surface molecularly imprinted polymers. Issue 15 (2nd February 2016) - Wang, Yanhui; Duan, Huimin; Li, Leilei; Wang, Xiaojiao; Li, Jianbo; Bu, Yanan; Luo, Chuannan
Abstract : In this paper, a new chemiluminescence sensor possessing high selectivity and sensitivity was established for determination of lysozyme using magnetic graphene oxide–multi-walled carbon nanotube surface molecularly imprinted polymer. Abstract : In this paper, a new chemiluminescence (CL) sensor possessing high selectivity and sensitivity was established for determination of lysozyme using magnetic graphene oxide–multi-walled carbon nanotube surface molecularly imprinted polymer (MGO–MWCNTs/SMIP). The MGO–MWCNTs/SMIP was characterized by X-ray diffraction (XRD), Fourier transform infrared (FT-IR) spectroscopy and scanning electron microscopy (SEM), and the maximum adsorption capacity of MGO–MWCNTs/SMIP to lysozyme was found to be 140 mg g −1 . The MGO–MWCNTs/SMIP was fixed into a glass tube and was connected to a chemiluminescent analyzer. Then a MGO–MWCNTs/SMIP-flow injection chemiluminescence (MGO–MWCNTs/SMIP-CL) sensor based on a luminol–NaOH–H2 O2 CL system was established for the determination of lysozyme. The proposed sensor with high selectivity and sensitivity responded linearly to the concentration of lysozyme over the range 5.04 × 10 −9 to 4.27 × 10 −7 g mL −1 and the detection limit was 1.90 × 10 −9 g mL −1 (3 δ ). The recoveries ranged from 98% to 111% when determining lysozyme in eggs and the result was satisfactory. The advantageous properties of sensor hold the potential to be applied in protein analysis, analogizing to biological analysis.